Dynamic texture perception in plant-based yogurt alternatives: Identifying temporal drivers of liking by TDS. (December 2020) - Greis, Maija; Sainio, Taru; Katina, Kati; Kinchla, Amanda J.; Nolden, Alissa; Partanen, Riitta; Seppä, Laila
Abstract: As texture properties in novel food categories have a crucial role in consumer acceptance, mouthfeel profile of different plant-based yogurt-like semi-solid products were studied and compared to dairy yogurts. Mouthfeel properties of five plant-based yogurt-like products and two dairy yogurts were analyzed using temporal dominance of sensations (TDS) with consumers (n = 87). The attributes evaluated were thick, thin, creamy, watery, sticky, and foamy. Following TDS, overall liking and mouthfeel liking were evaluated using a 7-point hedonic scale. Temporal drivers of mouthfeel liking were studied using correspondence analysis and penalty-lift analysis with different time points during mastication. For penalty-lift analysis TDS data was analyzed as check-all-that-apply (CATA) data. Results from the present work show that mouthfeel perception in non-dairy yogurt alternatives is a dynamic process. Attributes typically used to describe dairy yogurts are also relevant for describing non-dairy yogurt alternatives. Yogurt alternatives and dairy yogurts can be similar and equally liked by their mouthfeel profile. Temporal drivers of liking in plant-based products are thickness and creaminess and temporal drivers of disliking are thinness and wateriness. In this study, the first dominant attributes were found to have a stronger impact on mouthfeel liking than the dominant attributes perceived later during mastication.